(untitled) (Scientia Agropecuaria, 2025)
Organic quinoa (Chenopodium quinoa Wild) cultivation embodies a holistic agricultural approach, integrating biological fertilizers to curtail reliance on insecticides and synthetic fertilizers and low levels of greenhouse gases. The objective of this paper was to identify the socioeconomic factors that determine smallholder farmer organic quinoa production. The socioeconomic factors of organic quinoa farmer in the district of San Jerónimo, Apurímac in Southern Peru associated with five groups of organic quinoa farmers. Primary data were collected from 109 smallholder farmers belonging to quinoa producers’ associations, using a non-experimental and cross-sectional study design, that was analyzed with descriptive, correlational statistics and a logistic regression method involving the evaluation of 13 independent variables. Motivational factors are identified through the application of a qualitative and quantitative sequence of mixed methods design. The results show that high price is the most important explanatory variable, and it is also the one that smallholders primarily consider when cultivating organic quinoa. The second most important variables motivating such farmers are social factors, mainly those related to health benefits, food quality and lastly environmental benefits. The variables: quinoa income, distance to the land, membership in an association, technical assistance and mixed (own and hired) labor had an inverse relationship with organic quinoa production while land ownership had a positive but less significant effect on the production of organic quinoa (p < 0.1). In conclusion, organic quinoa producers are primarily influenced by financial reasons, followed by considerations of sustainability and the desire to obtain healthy, pesticide-free food for self-consumption. These findings of important factors in the adoption of organic agriculture by producer associations and the motivational aspects found for its continued production could be considered in agricultural policy proposals in the face of a world with greater demands for food and environmental protection.